APPLYING THE ISLAMIC LAW FROM THE VIEWPOINT OF MAQĀSHID AL-SHARĪ’AH: ANALYZING LEGAL OPINIONS OF SRI LANKAN MUSLIM SCHOLARS - Mohammad Shihan; Abdul Hamid Mohamed Ali Zaroum (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
The Sharīʿah is of fundamental importance for all Muslims. No Muslim is exempted from following the Sharīʿah. However, the understanding of Islamic law is often too narrow and problematic for several reasons. Further, this situation is more critical in the Muslim minority context since it paves the ways to misunderstand and misinterpret the nature and purpose of the Sharīʿah. Therefore, applying Sharīʿah has become a controversial matter that harms people’s interests rather than serves them. Further, during the last few decades, there has been significant interest among the scholars of Sharī’ah in producing the Maqāsid al-Sharī’ah as a new methodology to interpret the texts of Sharīʿah. They propose Maqāsid al-Sharī’ah as general principles that open expansive rooms for applying Sharīʿah under its broad perspective. Acknowledging this background, the researcher examined the views of Sri Lankan Muslim scholars about applying Sharīʿah based on Maqāsid al-Sharī’ah’s viewpoint. Hence, the perceptions about the application of Sharīʿah are collected from selected Muslim scholars by conducting the interview. This study follows the qualitative method of data collection and content analysis method to reach the results and findings. Accordingly, the study reveals that the prevailing narrow perspective about Sharīʿah serves as an obstacle for the correct and beneficial application of the Sharīʿah and causes negative perceptions among the public. Consequently, the study concludes that the broad perspective of Sharī’ah opens a more expansive space for the application of Sharī’ah and largely helps cooperate and collaborate with other religious communities.